Occupational damage to nurses in Primary Health Care - Célia Regina da Silva Medeiros; Viviane Brasil Amaral dos Santos Coropes; Karla Gualberto Silva; Shino Shoji; Norma Valéria Dantas de Oliveira Souza; Maria Helena do Nascimento Souza; Sheila Nascimento Pereira de Farias (Rev Rene)
Objective: analyze the prevalence and types of occupational injuries among nurses working in the Family Health Strategy. Methods: cross-sectional study with 116 Family Health Strategy nurses. The Work-Related Damage Assessment Scale was used. For the analysis, Pearson’s chi-square test was performed, with a significance level of 0.05. Results: the prevalence of physical damage of 70.7% was associated with the risk of critical illness, the most serious symptoms of which were: sleep or appetite alterations, circulatory disorders, body aches (head, arm, back, legs). Social damage (21.6%) and psychological damage (11.2%) were classified as bearable risk. Conclusion: showed high prevalence of illness manifested by physical damage classified as critical risk: arm pain, changes in appetite and circulatory disorders and, classified as serious risk: headaches, leg pain, sleep changes, back and body pain.